The Perception and Production of Word-Initial Korean Stops by Native Speakers of Japanese. (September 2019) - Holliday, Jeffrey J
Previous studies have shown that non-native speakers of Korean not only have difficulty producing the word-initial three-way stop contrast, but also exhibit a wide range of production patterns. Because these studies have only investigated native (L1) speakers of English and Mandarin and given the overall paucity of research on non-native Korean, it is not yet clear how dependent these findings are on the particular native language under investigation. The current paper reinforces our empirical grounding via extension to L1 speakers of Japanese. It is shown that although naïve Japanese listeners consistently perceive Korean fortis stops as voiced, and Korean lenis and aspirated stops as voiceless, novice second language learners do not produce any significant difference among the three stop categories, despite producing clear differences between their native Japanese stop categories. Unlike in previous studies of L1 speakers of English and Mandarin, there was very little inter-speaker variation, and all speakers produced all Korean stops with long lag voice onset time.